2019
DOI: 10.5693/djo.01.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The current state of retinopathy of prematurity in India, Kenya, Mexico, Nigeria, Philippines, Romania, Thailand, and Venezuela

Abstract: Retinopathy of prematurity (ROP) is one of the leading causes of preventable blindness in children worldwide. Middle-income nations are currently experiencing epidemic levels of ROP, because greater access to neonatal intensive care units has improved survival rates of premature infants, but without sophisticated oxygen regulation. The epidemiology, screening infrastructure, treatment options, and challenges that these countries face are often tied to unique local socioeconomic, cultural, geopolitical, and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…The incidence of ROP varies considerably in different populations and ethnic groups, so much so that in India it fluctuates from 38 to 47%, Thailand reports prevalence between 14 and 33%, while in Mexico approximately 24% of childhood blindness occurs as a result of ROP. 16 In this study, the overall incidence of ROP in preterm infants was 33.3% (72 of 144), with 23.6% of these infants having severe ROP (stage 3) ( Tables 2 and 3 ). In a study conducted in 2010–2011 in the same city, an incidence of 19.06% was reported, 17 this increase in recent years is also evident in other Latin American countries.…”
Section: Discussionmentioning
confidence: 51%
“…The incidence of ROP varies considerably in different populations and ethnic groups, so much so that in India it fluctuates from 38 to 47%, Thailand reports prevalence between 14 and 33%, while in Mexico approximately 24% of childhood blindness occurs as a result of ROP. 16 In this study, the overall incidence of ROP in preterm infants was 33.3% (72 of 144), with 23.6% of these infants having severe ROP (stage 3) ( Tables 2 and 3 ). In a study conducted in 2010–2011 in the same city, an incidence of 19.06% was reported, 17 this increase in recent years is also evident in other Latin American countries.…”
Section: Discussionmentioning
confidence: 51%
“…A recent paper describes the current state of ROP in eight LMICs. 23 The incidence of ROP was not available for all countries. This incidence, mostly based on smaller studies in one institution, ranged from 14% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Thus, middle-income countries are currently suffering from an ROP epidemic while incidence is also increasing slowly in low-income nations. 5 Bowe et al found that ROP screening criteria may need to be adjusted according to the country’s NICU capabilities and unique challenges. 5 …”
Section: Introductionmentioning
confidence: 99%